1993
DOI: 10.1023/a:1018922114398
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In order to improve the therapeutic index of adapalene, a new drug under development for the treatment of acne, site-specific delivery to the hair follicles using 50:50 poly(DL-lactic-co-glycolic acid) microspheres as particulate carriers was investigated in vitro and in vivo. The percutaneous penetration pathway of the microspheres was shown to be dependent on their mean diameter. Thus, after topical application onto hairless rat or human skin, adapalene-loaded microspheres (5-microns diameter) were specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(35 citation statements)
references
References 4 publications
1
33
0
Order By: Relevance
“…On the other hand, despite of much bigger size, poly(D,L-lactic-co-glycolic acid) (PLGA) microparticles of several microns were found even in the upper epidermis, 24 h after applying them a porcine skin [23]. A similar result was obtained by Rolland et al with porcine skin and microparticles [24]. The porcine skin is hairy and the follicular ducts, of which diameter is tens of micron, are proposed to the path way for the penetration of the microparticles.…”
Section: 7supporting
confidence: 71%
“…On the other hand, despite of much bigger size, poly(D,L-lactic-co-glycolic acid) (PLGA) microparticles of several microns were found even in the upper epidermis, 24 h after applying them a porcine skin [23]. A similar result was obtained by Rolland et al with porcine skin and microparticles [24]. The porcine skin is hairy and the follicular ducts, of which diameter is tens of micron, are proposed to the path way for the penetration of the microparticles.…”
Section: 7supporting
confidence: 71%
“…It was found that microparticles ranging from 3 -10 µm selectively penetrate the follicular ducts, whereas particles larger than 10 µm remain randomly distributed in the hair follicles and stratum corneum [130]. Moreover, 5 µm PLGA microparticles were visualized in the follicular ducts, while 1 µm was randomly distributed into the stratum corneum and hair follicles.…”
Section: Skin Drug Deliverymentioning
confidence: 99%
“…Finally, the role of skin appendages is sometimes neglected due to the fact that they only represent 0.1% of the skin surface [130]. It was found that microparticles ranging from 3 -10 µm selectively penetrate the follicular ducts, whereas particles larger than 10 µm remain randomly distributed in the hair follicles and stratum corneum [130].…”
Section: Skin Drug Deliverymentioning
confidence: 99%
“…increased bioavailability, drug targeting within the skin etc.) is currently under debate [26, 50, 51, 52, 53]. In clinical practice, the question is often asked whether creams, gels, ointments or liposomes are better in delivering a drug to the skin in terms of promoting the drug absorption and therapeutic effect [54].…”
Section: The Vehicle – Pharmaceutical Carrier Of Dermatological Agentsmentioning
confidence: 99%